2000
DOI: 10.1097/00000542-200002000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Action in the Spinal Cord Blunts Electroencephalographic and Thalamic–Reticular Formation Responses to Noxious Stimulation in Goats

Abstract: Isoflurane blunted the EEG and MRF-thalamic response to noxious stimulation in part via an action in the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
5
33
1
2
Order By: Relevance
“…This idea was further supported by animal studies. [9][10][11][12][13][14] In particular, in a series of works in goats, Antognini and colleagues 9-13 elegantly showed that pharmacological blockage of the spinal cord depressed the activating action of the forebrain reticular formation on cortical EEG. Depression of brainstem activity by epidural anesthesia was also confirmed in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea was further supported by animal studies. [9][10][11][12][13][14] In particular, in a series of works in goats, Antognini and colleagues 9-13 elegantly showed that pharmacological blockage of the spinal cord depressed the activating action of the forebrain reticular formation on cortical EEG. Depression of brainstem activity by epidural anesthesia was also confirmed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The sedative effect of spinal anesthesia could be due to the loss of somatosensory inputs to the brain, as suggested by animal studies. [9][10][11][12][13][14] Therefore, at least in principle, spinal cord injury should have the same sedative effects as spinal anesthesia. Somewhat surprisingly, it is not a common clinical practice to consider that spinal cord injury patients might have lower anesthetic requirements than patients with intact spinal cord, possibly because of lack of studies directly addressing the problem.…”
Section: Introductionmentioning
confidence: 99%
“…O estímulo doloroso durante a anestesia, outrora adequada, resulta em aumento da atividade neuronal na formação reticular e dessincronização do EEG, o que indica um desvio em direção ao despertar 39 . Os anestésicos voláteis bloqueiam impulsos nociceptivos na medula espinhal, diminuindo a transmissão ascendente da informação dolorosa que estimularia o despertar 14,[40][41][42] . O resultado final é um efeito sobre o estado de alerta do paciente que afeta o nível de consciência e amnésia durante a anestesia.…”
Section: Influência Da Medula Espinhal Sobre O Encéfalounclassified
“…Quando o isoflurano é administrado seletivamente ao encéfalo, a aplicação de um estí-mulo nocivo aumenta a atividade neuronal na formação reticular e no tálamo, e causa dessincronização do EEG. Por outro lado, a administração seletiva do anestésico à ME lentifica os sinais eletroencefalográficos corticais, enquanto a redução gradual da concentração de isoflurano na medula associa-se a um aumento das respostas de neurônios da formação reticular à estimulação dolorosa 42 . Esses resultados reafirmam o papel da medula espinhal na regulação da atividade supra-espinhal ao modular os estímulos ascendentes nociceptivos.…”
Section: Influência Da Medula Espinhal Sobre O Encéfalounclassified
See 1 more Smart Citation